Education incentive scheme to aid new students - Nor Hidayah, Mohamad (2017)
22 new student have been selected to receive Education Incentive Scheme in this 2017/2018 academic year. They were shortlisted by Student Affairs & Alumni Department based on criteria that they comes from a very poor family and facing financial issue. This aid is to help them in preparing basic need to furthering their studies here in UMP.